Mossbauer spectroscopic investigations of nanophase iron oxides synthesized by thermal plasma route - Nagar, Harshada; Kulkarni, Naveen V.; Karmakar, Soumen; Sahoo, B.; Banerjee, Indrani; Chaudhari, P. S.; Pasricha, R.; Das, A. K.; Bhoraskar, S. V.; Date, Sadgopal K.; Keune, W. (Materials Characterization, 2008)
Magnetic nanoparticles of iron oxide were synthesized by transferred arc plasma induced gas phase condensation method. Structural, morphological and magnetic studies of the as synthesized powder were carried out using X-ray diffraction, transmission electron microscopy and Mossbauer spectroscopy. These studies have revealed the simultaneous nucleation and condensation of different magnetic phases with a broad size distribution of the nanoparticles which is peaked at 30-50 nm and ranges from 10 nm to 80 nm. 57 Fe Mossbauer spectra recorded at various temperatures (5 K-300 K) in presence of external magnetic field (at 5 K) have suggested the presence of different phases of iron oxide with sizable amounts of gamma-Fe2O3 and alpha-Fe2O3 in addition to Fe3O4. The relative concentrations of these phases have been obtained by a self consistent spectral area analysis and were found to be 44:22:34 (%). (C) 2007 Elsevier Inc. All rights reserved.
Keywords: iron oxides; Mossbauer spectroscopy; phase analysis; plasma synthesis

Magnetic properties of thermal plasma synthesized nanocrystalline nickel ferrite (NiFe2O4) - Nawale, Ashok B.; Kanhe, Nilesh S.; Patil, K. R.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Journal of Alloys and Compounds, 2011)
A rapid synthesis method is reported for magnetic nanoparticles of nickel ferrite involving thermal plasma assisted vapor phase condensation process. The as-synthesized samples were characterized by X-ray Diffraction, Transmission Electron Microscopy, Vibrating Sample Magnetometer and X-ray Photoelectron Spectroscopy techniques. The average particle size was determined from the TEM micrographs and found to be around 30 nm. The effects of reactor parameters on the magnetic and structural properties have been evaluated, to find the optimized parameters so as to achieve the highest values of saturation magnetization and coercivity. Reasonably high saturation magnetization (48 emu/g) has been assigned to the high degree of crystallinity, achieved on account of high temperature during the growth, and the cation redistribution. The high value of coercivity (1150e) is explained on the basis of possible lattice defects arising from the cation redistribution. Detailed analysis of cation distribution using the XRD line intensity data leads to the conclusion that these samples are iron deficit and nickel rich. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: crystal structure; Magnetic measurements; Magnetization; Nanostructured materials; TEM

Magnetic properties of nanocrystalline CoFe2O4 synthesized by thermal plasma in large scale - Nawale, A. B.; Kanhe, Nilesh S.; Patil, K. R.; Reddy, V. R.; Gupta, A.; Kale, B. B.; Bhoraskar, S. V.; Mathe, Vikas L.; Das, A. K. (Materials Chemistry and Physics, 2012)
The paper reports the large scale synthesis of nanoparticles of CoFe2O4 using thermal plasma reactor by gas phase condensation method. The yield of formation was found to be around 15 g h(-1). The magnetic properties of CoFe2O4, synthesized at different reactor powers, were investigated in view of studying the effect of operating parameters of plasma reactor on the structural reorganization leading to the different cation distribution. The values of saturation magnetization, coercivity and remanent magnetization were found to be influenced by input power in thermal plasma. Although the increase in saturation magnetization was marginal (61 emu g(-1) to 70 emu g(-1)) with increasing plasma power; a significant increase in the coercivity (552 Oe to 849 Oe) and remanent magnetization (16 emu g(-1) to 26 emu g(-1)) were also noticed. The Mossbauer spectra showed mixed spinel structure and canted spin order for the as synthesized nanoparticles. The detailed analysis of cation distribution using the Mossbauer spectroscopy and X-ray photoelectron spectroscopy leads to the conclusion that the sample synthesized at an optimized power shows the different site selective states. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic materials; magnetic properties; Mossbauer spectroscopy; Nanostructures